A Grounded Theory Approach to Understanding Jombang Government Strategy in Facing the Era of Digitalization - Khumairoh, Devy Riesta Zuhrotul; Nukyanto, Damainsa Prahesti (Universitas Airlangga, 2024)
In 1967, Glaser and Strauss created a book entitled